PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KSPPS BMT BEN SEJAHTERA - Sikin, Sikin; Faozan, Akhmad (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The positive growth of KSPPS BMT Ben Sejahtera (BMT BEST) over the last ten years is closely related to employee performance. These performance results are closely influenced by organizational culture and work environment. In realizing the vision and mission of BMT BEST, research is needed to discuss the influence of organizational culture and work environment on employee performance at BMT BEST. The research involved a research sample of 82% of all employees. The organizational culture variable studied is the culture that is the value of KSPPS BMT Ben Sejahtera, known by the acronym SEJAHTERA, which differentiates it from other research. The research results show that there is a positive influence of PROSPEROUS organizational culture and the Work Environment has a partial positive influence on employee performance with a significance value of less than 0.05 (respectively sig. organizational culture = 0.008 and sig. work environment 0.003). Meanwhile, through the results of the f test, it was found that the SEJAHTERA Organizational Culture and Work Environment together had a positive influence on Employee Performance with a sig. 0,000. The conclusion of this study accepts all research hypotheses.